Remote sensing UAV/drones and its applications for urban areas: a review - Hj. Mohd. Noor, Norzailawati; Abdullah, Alias; Mazlan, Hashim (Institute of Physics Publishing, 2018)
The rapid development and growth of drones as a remote sensing platforms as well as advances in the miniaturization of instruments and data systems, have resulted in an increasing uptake of this technology in the urban areas and remote sensing social community. This paper attempt to review a development of UAV/Drone remote sensing applications in urban areas and it can resolve issues respectively. The classification, design methods and challenges has been discussed appropriately and at the end we suit to urban applications. We found that the evolution of UAV/drone based remote sensing is efficient to solve an urban issues nowadays simultaneously ensure the sustainability and resiliency of urban areas.